POLA MIGRASI DAN KARAKTERISTIK MIGRAN BERDASARKAN HASIL SENSUS PENDUDUK 2010 DI PROVINSI BALI - Ketut Sudibia; Nyoman Dayuh Rimbawan; Ida Bagus Adnyana (PIRAMIDA, 2012)
The population of Bali tends to increase from one period to another period. It’s shown from the result of population census, namely volkstelling that conducted in 1930 in the era of Dutch colonial until the latest population census in 2010. During the New Order era the government succeeded to control the population growth  which had been decreased from 1.71 percent per year during the period of 1971 to 1980 became 1.18 percent per year during the period of 1980 to 1990. This success was also supported by the decrease of fertility and mortality rates, and it’s still continuing until the regional autonomy era today. On the other hand the migration stream to Bali tends to increase, making this as determinating the high population growth achieving 2.15 percent per year along the period of the year 2000 to 2010. The objectives of this study are (1) to analyze population migration in Bali Province based on the population census in 2010; and (2) to analyze the characteristics of in-migration to Bali Province based on the population census the year 2010. The benefits of this study are (1) to provide inputs for the policy makers in the population field, especially in population migration and development aspects; and (2) to enhance the treasury of science, especially that closely related to migration study in Bali. The data sources that are used in this study are available from secondary data, especially from recent migration data that were collected in population census in 2010. Moreover, data are analyzed descriptively, by using frequency tables and cross tabulation. Findings of this study include (1) the recent in-migrant to Bali Province based on the result of population census in 2010 tended to compared to the data of population census in 2000; (2)  the pattern of recent in-migration to Bali in 2010, is not significantly different compared to the data of population census in 2000; (3) the patterns of recent out-migration from the result of population census in 2000 was the same as those of 2010; (4) the highest proportion recent in-migration stream to Bali came from East Java; (5) the selectivity factors of recent in-migrants are characterized in majority by people in productive ages, better educated people, and male; and (6) the majority of recent in-migrant are absorbed in the formal sector, however the majority of non-migrant are absorbed in the informal sector.